Development of Critical and Futuristic Awareness Evaluation Instruments in Science Learning Based on Emancipatory Approaches in Junior High Schools - Sheptian, Riky; Sutisna, Anan; Saefudin, Yetti Supriyati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates evaluation instruments that promote critical and futuristic awareness in middle school science through an emancipatory framework. Emphasizing the necessity for students to critically analyze scientific concepts and anticipate future outcomes, this research aims to develop tools that foster reflective thinking and social accountability. The instruments assess students' comprehension of scientific principles while encouraging awareness of social and environmental repercussions. By incorporating emancipatory educational principles, this research seeks to empower students as active learners, equipping them for the complexities of a swiftly evolving world. The findings underscore the importance of innovative evaluation techniques in enhancing science education.